Intergenerational Transmission of Risk Attitudes - A Revealed Preference Approach - Andrea Leuermann; Sarah Necker (Verein für Socialpolitik, 2010)
Using data the German Socio-Economic Panel (GSOEP), we investigate whether the willingness to take risks which is revealed via observed choices of occupation is transmitted from parents to children. Our approach resembles the one by Dohmen et al. (2008) who investigate the same question using stated preferences. As risk variable we use earnings risk measured by the cross-sectional coefficient of residual variation obtained from Mincerian wage regressions. We find that fathers' riskiness of the job chosen is a significant determinant of sons' occupational risk. Our results are robust to different specifications, underpinning the hypothesis of intergenerational transmission of risk preferences.
Keywords: J13; J62; D81; 330